Neonatal Nurses' Perceptions of Palliative Care in the Neonatal Intensive Care Unit. Issue 5 (September 2021) - Chin, Susan Di Nonno; Paraszczuk, Ann Marie; Eckardt, Patricia; Bressler, Toby
Abstract: Purpose: Neonatal palliative care is widely endorsed as an essential aspect of neonatal intensive care unit (NICU) practice, yet inconsistencies in its use continue to exist. We examined neonatal nurses' perceptions of barriers and facilitators to palliative care in their NICU setting. Study Design and Methods: A cross-sectional design using the Neonatal Palliative Care Attitude Scale (NiPCAS ™© ) was administered using an online survey distributed to neonatal nurses through the Association of Women's Health, Obstetric and Neonatal Nurses (AWHONN) and National Association of Neonatal Nurses (NANN). Parametric statistical analyses were conducted to explore relationships between unit policy and neonatal palliative care (NPC) education, and the nurses' perceptions. Results: Ninety-nine of 1, 800 AWHONN members who identified as NICU nurses completed the survey, representing a response rate of 5.5% and 101 of 4, 000 NANN members who subscribe to the MYNANN message boards completed the survey, reflecting a 2.5% response rate. N = 200 surveys were completed with minimal data missing, resulting in a final sample of 200. Exploratory factor analysis yielded these subconstructs: Unit Culture, Resources, and Perceived Inappropriate Care. Barriers identified were Perceived Inappropriate Care and Societal Understanding of NPC. A positive correlation was noted for NiPCAS ™© scores and unit culture support ( r (185) = .66, n = 187, p < .01), unit NPC policy ( r (184) = .446, n = 186, p < .01), and NPC education ( r (185) = .373, n = 187, p < .01). Clinical Implications: Nurses who work in a NICU with an NPC policy and who have received palliative care education demonstrated more favorable attitudes toward NPC. Policy and educational programs are important strategies to promote high-quality care for high-risk infants and their families. Abstract : Guidelines for neonatal palliative care have existed for over 20 years, yet less than 4% of children who meet criteria for palliative care receive these services. Neonatal intensive care unit nurses are uniquely positioned to influence end-of-life care for infants and their families' experiences. N = 200 neonatal intensive care nurses in the United States participated in a survey about neonatal palliative care. Nurses who work in a unit with a neonatal palliative care policy and who have received palliative care education demonstrated more favorable attitudes toward neonatal palliative care. Policy and educational programs are important strategies to promote high-quality care for high-risk infants and their families.